Home advantage in elite handball: the impact of the quality of opposition on team performance - Lago-Penas, C.; Gomez, M. A.; Viano, J.; Gonzalez-Garcia, I.; Fernandez-Villarino, M. de Los Angeles (International Journal of Performance Analysis in Sport, 2013)
The aims of this study were: (1) to examine the influence of game location and team quality on performance indicators in elite handball and (2) to analyze the home advantage effect in different game contexts according to the ability of both teams (strong, intermediate and/or weak). The sample included all 240 matches from the Spanish Professional Handball League (ASOBAL League) during the 2012/13 season. The home advantage was 63.10%, but this effect depends on the particular context of the game. Results identified those critical game-related statistics that are affected by playing at home or away (6m Goal Effectiveness, 9m Goal Effectiveness, Fast Break Goals, Field Total Shots, Steals, 6m Goalkeeper Effectiveness, 9m Goalkeeper Effectiveness and Total Goalkeeper Effectiveness